2002
DOI: 10.1023/a:1021401826554
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cogrinding with a beta-CD of higher water content can be an effective method to prepare fine drug particles at the submicron level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…[10][11][12] We also found that moisture content in the co-grinding process was an important factor and a suitable moisture condition during co-grinding was indispensable for nanoparticle formation.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…[10][11][12] We also found that moisture content in the co-grinding process was an important factor and a suitable moisture condition during co-grinding was indispensable for nanoparticle formation.…”
mentioning
confidence: 82%
“…In the past few years, there are many publications focusing on the preparation of drug particles at the nanometer level by co-grinding with additives. [7][8][9][10][11][12][13][14] In previous studies, we have reported the formation of pranlukast nanoparticle with mean particle size around 200 nm by co-grinding with CDs.10) Co-grinding with CDs could be applied as a nanoparticle preparation method for various kinds of poorly water-soluble drugs. [10][11][12] We also found that moisture content in the co-grinding process was an important factor and a suitable moisture condition during co-grinding was indispensable for nanoparticle formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Improved dissolution by co-grinding has been described in many reports regarding dry milling, 18),20),22), [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] although some studies utilized the formation of amorphous particles by co-grinding. 18), [25][26][27][28][29][30][31][32][33][34] The unintentional formation of amorphous particles is undesirable because the quality of the powder can easily change during storage. Therefore, the present study demonstrates that co-grinding with PVP by LN2 milling is a powerful tool for improving the dissolution of poorly water-soluble phenytoin without the formation of amorphous particles.…”
Section: Dissolution Of Co-ground Mixturesmentioning
confidence: 99%
“…[2][3][4] It is clinically used in the treatment of gastroeosophageal reflux disease (GERD), gastric and duodenal ulcers and ZollingerEllison syndrome. [5] Formation of cyclodextrin inclusion complex is of immense application in improving the physical [6] , chemical [7] and thermal stability [8] of drugs. Cyclodextrins are toroidal shaped presenting hydroxyl groups to the external environment and hydrophobic functionality lining interior of the cavity.…”
Section: Introductionmentioning
confidence: 99%